Top-Ten Tips for Imaging the Brachial Plexus with Ultrasound and MRI - Griffith, James F.; Lalam, Radhesh Krishna (Seminars in Musculoskeletal Radiology, 2019)
When it comes to examining the brachial plexus, ultrasound (US) and magnetic resonance imaging (MRI) are complementary investigations. US is well placed for screening most extraforaminal pathologies, whereas MRI is more sensitive and accurate for specific clinical indications. For example, MRI is probably the preferred technique for assessment of trauma because it enables a thorough evaluation of both the intraspinal and extraspinal elements, although US can depict extraforaminal neural injury with a high level of accuracy. Conversely, US is probably the preferred technique for examination of neurologic amyotrophy because a more extensive involvement beyond the brachial plexus is the norm, although MRI is more sensitive than US for evaluating muscle denervation associated with this entity. With this synergy in mind, this review highlights the tips for examining the brachial plexus with US and MRI.
Keywords: brachial plexus; ultrasound; magnetic resonance imaging; inflammation; trauma